LCA study and testing of a photovoltaic ceramic tile prototype. (February 2015) - Belussi, Lorenzo; Mariotto, Matteo; Meroni, Italo; Zevi, Chiara; Svaldi, Sandra Dei
Abstract: The article describes the analysis of the environmental impact of a Building Integrated PhotoVoltaics (BIPV) module developed within the research project "BIPV-Building Integrated Photovoltaics, Piastrelle ceramiche fotovoltaiche per involucri edilizi sostenibili". The aim of the project is the development and the implementation of photovoltaic BIPV ceramic modules to be used in buildings for the construction of active envelopes. In particular, one of the research lines of the project involves the construction of BIPV ceramic modules by depositing a thin film of amorphous silicon on a ceramic support. Research and development activities previously carried out by the Ceramic Centre of Bologna in collaboration with other companies have led to the production of prototype of a ceramic photovoltaic module. The project aims to the optimization and the industrialization of the module. Other BIPV modules (for example made on glass sheets) have been used in the construction industry for over 20 years as an integral part of the building, in both horizontal (roofs and skylights) and vertical components (facades). The use of these modules allows the realization of active technical elements, reducing the use of raw materials. The environmental impact assessment of the BIPV ceramic module was conducted through the life-cycle approach, in accordance with the international standards of the ISO 14040 series, in order to define the eco-profile, identifying the processes with the greatest impacts and suggesting improvements. The environmental profile thus obtained was then compared with that of other photovoltaic modules, in order to assess the environmental performance compared to existing technologies. Highlights: We describe the LCA study of a ceramic BIPV module. We compare the environmental profile of the ceramic BIPV module with other conventional PV modules. We apply the NOCT method to calculate the energy production of the PV module.